2021
DOI: 10.3390/ma14195469
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of Quantum Dots-Labelled Halloysite Nanotubes: A Caenorhabditis elegans In Vivo Study

Abstract: Halloysite is a promising building block in nanoarchitectonics of functional materials, especially in the development of novel biomaterials and smart coatings. Understanding the behavior of materials produced using halloysite nanotubes within living organisms is essential for their safe applications. In this study, quantum dots of different compositions were synthesized on the surface of modified clay nanotubes, and the biodistribution of this hybrid material was monitored within Caenorhabditis elegans nematod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…Commun., 2022, 58, 7719-7729 | 7727 bacterial food. 53,75 This indicates that the exposure to photoactive nanoparticles stabilized on halloysite does not cause a gross behavioral defect in the organism. They show no acute toxic effects on reproduction ability, life cycle, and behavior of model nematodes.…”
Section: Feature Article Chemcommmentioning
confidence: 96%
See 2 more Smart Citations
“…Commun., 2022, 58, 7719-7729 | 7727 bacterial food. 53,75 This indicates that the exposure to photoactive nanoparticles stabilized on halloysite does not cause a gross behavioral defect in the organism. They show no acute toxic effects on reproduction ability, life cycle, and behavior of model nematodes.…”
Section: Feature Article Chemcommmentioning
confidence: 96%
“…12 CuS nanoparticles could be synthesized on the surface of halloysite modified with aminosilanes and azines of various compositions using methods similar to CdS NPs stabilization on clay nanotubes. 75–77 Our preliminary studies showed that depending on the modification agent (aminosilane or ketazine) CuS NPs stabilized on nanotubes possess different antibacterial activity under visible light against S. aureus . Halloysite modification could be applied to change the charge and chemistry of clay tubes and tune the structure and activity of nanomaterials based on it.…”
Section: Halloysite Based Photoactive Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 By variation of synthesis parameters, one can produce bright colored and biosafe nanoclay markers for cell labeling. 31,32 Such nanotubes with incased quantum dots showed low toxicity to eukaryotic cells and to model nematodes such as C. elegans. CdSe quantum dots were selectively loaded inside the nanoclay lumens driven by the electrostatic interaction of negatively charged CdSe particles and positively charged lumens (Fig.…”
Section: Selective Metal Modification Inside and Outside The Tubesmentioning
confidence: 99%
“…We developed the Ouali model by consid- Recently, ceramic nanoparticles have attracted much interest in the academic research community [23][24][25][26][27][28][29][30][31][32]. Alumino-silicate and nanotubular HNT, for example, have the composition of Al 2 (OH) 4 Si 2 O 5 (2H 2 O) and few hydroxyl groups on their surface [30,[33][34][35][36][37]. They normally have a single-tube construct, which can be dispersed in any solvent medium because of siloxane and their few hydroxyl groups, which simplifies the distribution and development of hydrogen bonding [38].…”
Section: Introductionmentioning
confidence: 99%